Profit maximization: The ethical mandate of business - Primeaux, Patrick (Journal of business ethics, 1994)
The authors propose a model for business ethics which arises directly from business practice. This model is based on a behavioral definition of the economic theory of profit maximization and situates business ethics within opportunity costs. Within that context, they argue that good business and good ethics are synonymous, that ethics is at the heart and center of business, that profits and ethics are intrinsically related.